USING THE VIRTUAL CLASSROOM BY TEACHERS OF THE SCHOOL OF ACCOUNTING (2014) - Carreño Escobedo, Jorge Raúl (2015)
Electronic media learning are becoming the most common means used by many educational institutions nationally and internationally. For that reason, some of the faculties of the National University of San Marcos are taking advantage of the virtual classroom use; in that case, the School of Accounting has been using and benefitting from the online learning resource for some years. This virtualization tool called Moodle 2.5 allows both teachers and students, and other guests to receive access to e-learning. Given the resource utility of e-learning (online), it evidenced the efficiency of the virtual classroom by teachers of the School of Accounting Sciences in September 2014, through certain criteria. The population considered was based on 105 teachers where a group of 30 teachers was sampled, they regularly attended the training course in Virtual Classroom: Tools for university teaching.